Evolutionary History of Endogenous Human Herpesvirus 6 Reflects Human Migration out of Africa. (28th July 2020) - Aswad, Amr; Aimola, Giulia; Wight, Darren; Roychoudhury, Pavitra; Zimmermann, Cosima; Hill, Joshua; Lassner, Dirk; Xie, Hong; Huang, Meei-Li; Parrish, Nicholas F; Schultheiss, Heinz-Peter; Venturini, Cristina; et al.
Abstract: Human herpesvirus 6A and 6B (HHV-6) can integrate into the germline, and as a result, ∼70 million people harbor the genome of one of these viruses in every cell of their body. Until now, it has been largely unknown if 1) these integrations are ancient, 2) if they still occur, and 3) whether circulating virus strains differ from integrated ones. Here, we used next-generation sequencing and mining of public human genome data sets to generate the largest and most diverse collection of circulating and integrated HHV-6 genomes studied to date. In genomes of geographically dispersed, only distantly related people, we identified clades of integrated viruses that originated from a single ancestral event, confirming this with fluorescent in situ hybridization to directly observe the integration locus. In contrast to HHV-6B, circulating and integrated HHV-6A sequences form distinct clades, arguing against ongoing integration of circulating HHV-6A or "reactivation" of integrated HHV-6A. Taken together, our study provides the first comprehensive picture of the evolution of HHV-6, and reveals that integration of heritable HHV-6 has occurred since the time of, if not before, human migrations out of Africa.